THE EFFECT OF LEARNING OUTCOMES ENTREPRENEURSHIP COURSES AND TYPES OF WORK PARENTS ON INTEREST IN STUDENT ENTREPRENEURSHIP - Hani Nurlaily (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
This study aims to find out 1) The effect of learning outcomes on entrepreneurship courses on the interest of student entrepreneurship 2) The effect of the type of work of parents on the interests of student entrepreneurship 3) The effect of learning outcomes on entrepreneurship courses and the type of work parents have on the interests of student entrepreneurship. This study uses a quantitative approach with multiple linear regression analysis using SPSS 23.0 software. A sample of 163 students from Unesa's economic education department who had programmed entrepreneurship courses using proportional random sampling techniques. The data collection technique was carried out using a questionnaire with a Guttman scale model. The results of the study show that 1) There are influences on the learning outcomes of entrepreneurship courses on the interests of student entrepreneurship 2) There is no influence of the type of work of parents on the interests of student entrepreneurship 3) There is a simultaneous influence between learning outcomes in entrepreneurship courses and the type of work parents have to interest in entrepreneurship student.